ВЕРТИКАЛЬНОЕ РАСПРЕДЕЛЕНИЕ ПЛАНКТОНА В СТРАТИФИЦИРОВАННОМ ГИПЕРГАЛИННОМ ОЗЕРЕ БОЛЬШОЕ ЯРОВОЕ, АЛТАЙСКИЙ КРАЙ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In article it is considered vertical plankton distributions at a temperature gradient, as an ode from the major characteristics of an ecosystem of shallow salty lakes. During the summer period in the lake Big Summer (Altay territory) is established thermal stratification which causes the authentic stratified distribution of population Artemia sp.